Preeclampsia: modern laboratory capabilities for the prognosis of the risk of this complication in the first trimester - Рыкова, О. В. (REPRODUCTIVE ENDOCRINOLOGY, 2014)
Preeclampsia is a pathological syndrome that develops during pregnancy and complicates 3–5% of all pregnancies, being one of the main causes of premature birth, maternal and perinatal mortality. Fetal Medicine Foundation recommended to assess the risk of developing preeclampsia used in the first trimester of a comprehensive assessment, including data about the pregnant woman, the presence of clinical risk factors, ultrasound features, data on the level of blood pressure, as well as level of two biochemical markers: placental growth factor (PlGF) and plasma protein A, associated with pregnancy (PAPP-A) that significantly reduced when there is a high risk of preeclampsia. This assessment allows predicting the development of early preeclampsia in 90% of cases, the level of false-positive results in 5% of cases and should be performed in all pregnant women in the first trimester in terms of 11–13 weeks.